An Analysis of Mathematical Problem-Solving Skills of Junior High School Students - Gunawan, Rilla Gina; Mudjiran, Mudjiran; Suherman, Suherman; Yerizon, Yerizon; Musdi, Edwin; Armiati, Armiati; Rozika, Eri (Universitas Islam Negeri Raden Intan Lampung, 2023)
This study examines the level of mathematical problem-solving abilities among students, specifically focusing on contextual problems related to plane geometry. A qualitative method with a descriptive approach was employed, involving data reduction, data presentation, and conclusion drawing. Problem-solving abilities were measured using a test comprising two questions. The results indicate a low level of proficiency among students of Public Junior High School 10 in Sungai Penuh City, with an average score of 22.28 and a success rate of 15.23%. These findings underscore the need for enhancing students' problem-solving skills. The critical role of teachers in the learning process and the use of effective learning media are anticipated to significantly improve students' abilities. For future research, it is recommended to conduct a deeper analysis of factors influencing these low problem-solving skills, such as curriculum, teaching methods, and the student's learning environment, and to test educational interventions that could enhance problem-solving skills.